The Effect of Operating Costs on Net Profit in Automotive Sector Companies Listed on the Indonesia Stock Exchange in the 2021-2024 Period - Virna Bahu; Sahmin Noholo; Siti Pratiwi Husain (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of operating costs on net profit in automotive sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. A quantitative approach with simple linear regression analysis was applied. The sample consists of 11 companies selected through purposive sampling, resulting in 44 firm-year observations. Secondary data were collected from audited annual financial reports published on the IDX.The results show that operating costs have a positive and significant effect on net profit, with a t-value of 34.033 > t-table 2.018 and a significance value of 0.000 < 0.05. The adjusted R² value of 0.821 indicates that 82.1% of the variation in net profit can be explained by operating costs. All classical assumption tests were satisfied, confirming the validity of the regression model.The findings suggest that operating costs, when managed efficiently, contribute to net profit growth in the automotive sector. This study provides empirical evidence for managers and investors regarding cost management strategies.